An Application of Vector Error Correction Model Approach in Explaining the Impact of Foreign Direct Investment on Economic Growth of Asian Developing Countries - Ali, Najaf; Mingque, Ye (International Journal of Economics and Financial Issues, 2018)
This study has binal purposes, the first one is to inspect the interrelation between foreign direct investment and economic growth and the second one is to scrutinize the effect of foreign direct investment on economic growth of Sri Lanka, Pakistan, Philippine and Thailand using panel data for the period of 1990-2014.This study applies Johansen Cointegration test and vector error correction model (VECM) analysis as evaluation techniques. The facts show that there is a positive, significant and long period relationship among FDI and economic growth. The results also discloses there is a long-term Granger causality running from foreign direct investment, gross capital formation, government consumption, trade openness and labor to GDP. Keywords: FDI, Asian developing countries, Vector Error Correction Model JEL Classifications: F10, F19, F21